SOME ASPECTS OF CALCULATION OF JOINT OPERATION OFSEWAGE SLUDGE PUMPS AND PIPELINE NETWORKS - Morozov, Viktor Andreevich; Morozov, Aleksandr Viktorovich; Morozova, Elena Nikolaevna (Journal of Applied Engineering Science, 2017)
The article considers the issues of joint operation of centrifugal pumps and networks for sewage sludge (SS) the flow of which is described by the Bingham plastic model. The authors present the results of the experimental studies of SS pumps operation and a formula for working out pump performance parameters for SS with different concentrations. To determine the design point of the joint operation of pumps and networks we used the dependence of hydraulic pressure losses in the pipeline by means of generalized Reynolds number taking into account SS viscoplastic properties. The results of experimental and design data for centrifugal SS pump performance parameters are given.